IMPLEMENTASI SISTEM INFORMASI ABSENSI GURU PADA SMK NEGERI 4 KOTA SORONG - Juneth N. Wattimena; Peter Manuputty (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2021)
SMK Negeri 4 is a vocational-based high school located in Sorong, West Papua - Indonesia. Paper-based attendance system for teachers is considered to be a major challenge as it is not effective in database management. In the era of technological development, analysis of the productivity and efficiency of teacher and administrator in schools required a web-based administration system. The purpose of this activty is to design and build an online presence system for employees at SMK Negeri 4 using the waterfall method. This procedure is done in the sequentially. The results of the design are accurate, quality and effective data in administrative archiving, and the report can be directly controlled by head-master. The conclusion is web-based attendance system for teacher at SMK Negeri 4 makes it easy to access information and efficient data archiving